Testing the Antioxidant Potential of Mango Leaves (Mangifera indica) from Bandar Khalipah Village, Deli Serdang Regency Using the FRAP Method - Tambunan, Pravil Mistryanto; Sihotang, Supran Hidayat (Pendidikan Kimia FKIP Universitas Jambi, 2024)
This study aims to identify and analyze the antioxidant potential of mango leaves (Mangifera indica) sourced from Bandar Khalipah Village, Deli Serdang Regency. Mango leaves are known to contain various secondary metabolites such as flavonoids, tannins, saponins, alkaloids, glycosides, as well as steroids and triterpenoids, which play a crucial role as natural antioxidants. The extraction process was carried out by maceration using 96% ethanol, yielding a thick extract with a rendement of 117%. Phytochemical screening indicated the presence of active compounds in the mango leaf extract. Antioxidant capacity was measured using the FRAP (Ferric Reducing Antioxidant Power) method, resulting in an average value of 151.7 mgAAE/g extract. These results suggest that mango leaves have significant potential as a natural antioxidant source that can be utilized to prevent damage caused by free radicals in the body. This study reinforces the use of mango leaves as a natural alternative for public health.